Popular Egyptian cinema : gender, class, and nation - Shafik, Viola, 1961- (American University in Cairo Press, 2007)
Viola Shafik examines popular and commercial movies from Egypt's film industry, including a number of the biggest box-office hits widely distributed in Egypt and the Arab world. She examines these films against the backdrop of the country's overall socio-political development, from the emergence of the film industry in the 1930s, through the Nasser and Sadat eras, up to the era of globalization.